2018
DOI: 10.1038/s41418-017-0041-z
|View full text |Cite
|
Sign up to set email alerts
|

Type I IFN operates pyroptosis and necroptosis during multidrug-resistant A. baumannii infection

Abstract: Multidrug-resistant Acinetobacter baumannii, a common pathogen responsible for nosocomial infections, is the main cause for outbreaks of infectious diseases, such as pneumonia, meningitis, and bacteremia, especially among critically ill patients. Epidemic A. baumannii is a growing public health concern as it is resistant to all existing antimicrobial agents, thereby necessitating the development of new therapeutic approaches to mount an effective immune response against this bacterial pathogen. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
49
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 51 publications
7
49
1
Order By: Relevance
“…GO enrichment showed that expression of pyroptosis related genes, such as Casp1 and Casp4 significantly increased, as well as necroptosis process related genes Mlkl and Ripk1 (Table S1). These data are consistent with the previous study showing that A. baumannii infection induced cell apoptosis, pyroptosis, and necroptosis in BMDM (13,14), DCs (27), and epithelial cells (28). The key mechanisms in regulating cell death presses in A. baumannii lung infection remain to be investigated.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…GO enrichment showed that expression of pyroptosis related genes, such as Casp1 and Casp4 significantly increased, as well as necroptosis process related genes Mlkl and Ripk1 (Table S1). These data are consistent with the previous study showing that A. baumannii infection induced cell apoptosis, pyroptosis, and necroptosis in BMDM (13,14), DCs (27), and epithelial cells (28). The key mechanisms in regulating cell death presses in A. baumannii lung infection remain to be investigated.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, more hypervirulent strains of A. baumannii are isolated and used to establish lethal mice model and more researchers explored the governing host factors associated with A. baumannii lethality (9,10). It has been reported that A. baumannii infection induced the production of proinflammatory cytokines TNFα, type I IFN, and IL-1β, which mediated cell death and lung pathology (11)(12)(13)(14). The induction of potent inflammatory immune response contributed to the mortality caused by A. baumannii.…”
Section: Introductionmentioning
confidence: 99%
“…Cell death during sepsis involves a large number of pro‐inflammatory cytokines which combine to form a “cytokine storm” . A study by Li et al revealed that type I IFNs control the transcription of key mediators of apoptosis, necroptosis, and pyroptosis signaling.…”
Section: Sting Signaling and Cell Deathmentioning
confidence: 99%
“…A. baumannii infection-induced IL-1β/IL-18 production was found to be entirely dependent on the activation of NLRP3 (NOD-, LRR-, and pyrin domain-containing protein 3)-ASC-caspase-1/caspase-11 pathway. The critical role of NLRP3 inflammasomes in the host innate defense against A. baumannii clinical isolates was confirmed in NLRP3-/- mice, whereas the NLRP3 inflammasome was dispensable for protection against A. baumannii type strains (Kang et al, 2017 ; Dikshit et al, 2018 ; Li Y. et al, 2018 ; An and Su, 2019 ). These results are intriguing because most A. baumannii ATCC type strains are clinical isolates and they can be as virulent as many fresh clinical isolates in mice (Harris et al, 2013 , 2017 ; Bruhn et al, 2015 ).…”
Section: Host Innate Immune Responses To a Baumanniimentioning
confidence: 96%